Peran Lembaga Legislatif dalam Mengawal Demokrasi di Indonesia: Tinjauan Hukum Tata Negara - Raudatun Nazwa; Alifya Zhafira; Annisa Hamdah; Mufti Wardani; Ahmad Muhajir; Anwar Hafidzi (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study examines the role of the legislative body in safeguarding and maintaining democracy in Indonesia from a constitutional law perspective. The research focuses on how the legislature carries out its functions of legislation, oversight, and budgeting to ensure democratic principles are upheld. It also assesses the legislature's role in holding the government accountable and balancing power with the executive and judiciary branches. The findings show that the legislature plays a significant role in creating transparent, accountable governance aligned with the constitution.